Goethite promoted anaerobic digestion of algal biomass in continuous stirring-tank reactors. (1st November 2015) - Yue, Zheng-bo; Ma, Ding; Wang, Jin; Tan, Juan; Peng, Shu-Chuan; Chen, Tian-Hu
Highlights: Addition of goethite enhanced the methane yield of algal biomass in CSTR. Goethite had a significant influence on the bacterial and archaeal community. Clostridium and Methanosaeta were the dominant strains in the goethite-dosed reactors. Abstract: With the depletion of fossil energy, third-generation biofuel feedstocks represented by micro- and macro-algae have significant advantages. It has been shown that anaerobic digestion of algae is a simple and cost-effective strategy. In this study, goethite was added to continuous stirred-tank reactors (CSTRs) to promote the methanogenesis of algal biomass. The results indicated that biogas and methane production increased by 16.1% and 24.1%, respectively. Goethite increased the conversion efficiency of the acidogenic and methanogenic phases. Goethite supplementation influenced the bacterial and methanogenic community significantly, which further enhanced the syntrophic effects between acidogenic and methanogenic microorganisms. The results confirmed that goethite could promote the anaerobic digestion of algal biomass in a CSTR, demonstrating its potential application to accelerate methane production process.